Local and systemic cellular immunity in early renal artery atherosclerosis - Kotliar, Carol Virginia (2012)
BACKGROUND AND OBJECTIVES: Modern imaging techniques have increased the incidental detection of renal atherosclerotic disease (RAD). Because immune activation may hasten RAD progression, identifying cellular immune markers might provide clues to clinical activity. In this study, cellular immune markers were assessed in early RAD. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Immune cell markers in peripheral blood of two groups of hypertensive patients with normal carotid and coronary arteries were evaluated: 28 patients had incidental RAD and 22 patients had normal renal arteries; 21 renal arteries obtained at necropsy from individuals with history of hypertension and tissue evidence of RAD were examined and matched with 21 individuals with normal renal arteries. Cell subpopulations were measured by flow cytometry in peripheral blood and direct cell count, respectively, using T and dendritic cells monoclonal antibodies. RESULTS: Peripheral blood of RAD patients showed increased numbers of cells expressing CD3, CD4, CD83, and CD86. CD4 to CD8 ratio was 8.3 ± 1.4 (RAD) to 3.4 ± 0.9 (normal; P<0.001). No differences were found in CD25, CD8, and S100 among groups. Postmortem samples from RAD showed increased CD3+, CD4+, CD86+, and S100+ cells, whereas CD25+ and CD8+ were unmodified between groups. CD4+ to CD8+ ratio was higher in the RAD(PM) group. CONCLUSIONS: These results are consistent with an increased expression of immune cell markers in early RAD. Additional studies will explore if they may potentially turn into treatment targets to prevent disease progression.